Modeling of heat transfer processes in ventilated enclosing structures in stationary conditions - Lymarenko, Oleksiy (Technology audit and production reserves, 2017)
One of the ways to increase the energy efficiency of the housing and communal enterprise and solve the problem of space heating is the construction of «Passive houses», which contain elements of structures that effectively absorb the energy of solar radiation. The object of the study is the «Passive house», which is a building in which thermal comfort (ISO 7730) is achieved solely by additional preheating (or cooling) of the fresh air mass. This is necessary to maintain high quality air in the rooms, without additional recirculation. The analysis of heat exchange processes in ventilated enclosing structures is carried out and the calculation methods for their design are analyzed. The application of passive solar heating technology in Ukraine's climatic conditions will provide up to 50 % of the heat needs. It is determined that the movement of outdoor air in the ES (open enclosing structures) along the wall of the house leads to heat loss, but air in the ventilated layer will prevent the formation and accumulation of condensate. This will allow in winter to maintain the thermal properties of the outer layer of insulation at home, reduce the cost of heat for heating and prevent the formation and development of fungal mold. The peculiarities of heat exchange processes in building structures with ventilated channels are studied. On the basis of the analysis of calculation methods for ES design, it can be stated that the classical method for evaluating heat exchange processes is based on the equations for the thermal balance of air for an infinitesimal volume dx. But when using this equation, it is impossible to take into account the distribution of radiant and convective heat flows, and also to estimate the effect of energy losses. The paper proposes a mathematical model that will allow to determine changes in air temperature along the ventilated layer of enclosing structures and to quantify the intake or loss of heat to the room during the cold season.